The expression of BMP4 and FGF2 in Wistar rats (Rattus norvegicus) post application of gourami fish (Osphronemus goramy) collagen - Chiquita Prahasanti; Niken Luthfiyya Arini; Kurnia Dwi Wulan; Onge Victoria Hendro; I Komang Evan Wijaksana; Noer Ulfah; Banun Kusumawardani; Padmini Hari; Shahabe Saquib Abullais (Dental Journal, 2023)
Background: Periodontitis is a chronic inflammatory disease of the periodontal tissue that is characterized by alveolar bone resorption. This occurs due to an imbalance of osteoblast and osteoclast during the bone formation and resorption processes. In order to obtain complete regeneration of periodontal tissue, bone grafting is frequently used in periodontal surgical therapy. Although each material has disadvantages, safe graft materials derived from animal sources can be employed as an alternative to bone graft materials. Osteoblast, osteoclast, calcified bone matrix, type I collagen, osteonectin, and hydroxyapatite can all be found in gourami scales, a form of food waste. BMP4 has osteoinduction functions, which are important in bone metabolism. Through angiogenic activity, FGF2 also contributes to periodontal regeneration. Purpose: The aim of the study was to assess the expression of BMP4 and FGF2 after the treatment group had been given gourami fish scale extract. Methods: Thirty-two experimental three-month-old male Wistar rats (150-200g) were randomly divided into four groups: a seven-day control group, a seven-day treatment group, a 14-day control group, and a 14-day treatment group. One mandibular incisor was extracted from each Wistar rat. The post-extraction socket was filled with blood for the control group and collagen extract for the treatment. Results: The one-way ANOVA test showed a significance level of 0.000 (p = <0.05). Conclusion: The expression of BMP4 and FGF2 increased after the application of collagen extract from gourami scales.